1995
DOI: 10.1007/bf00383150
|View full text |Cite
|
Sign up to set email alerts
|

Blood toluene as a biological index of environmental toluene exposure in the ?normal? population and in occupationally exposed workers immediately after exposure and 16 hours later

Abstract: Blood toluene was measured in a group of 100 workers occupationally exposed to a mean 8-h environmental toluene concentration of 128 micrograms/l (34 ppm), and in a group of 269 "normal" subjects without occupational exposure to toluene. The mean blood toluene of the workers at the end of the shift and the following morning, after 16 h, was 457 and 38 micrograms/l, respectively. The normal subjects had a blood toluene level of 1.1 micrograms/l. On the basis of the highly significant correlation between blood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The ACGIH has recommended a value of 50 µg/L in venous blood, collected prior to last shift of workweek 3) , as a biological index equivalent to the TLV of 188 mg/m 3 toluene. The ACGIH proposal has been confirmed by many researches and is in accordance with laboratory simulation models of exposure [22][23][24][25][26][27] . The in vitro blood/air partition coefficient for toluene at 37°C reported by the ACGIH Documentation of the biological exposure indices was included between 11.2 and 15.6 28) .…”
Section: Discussionsupporting
confidence: 55%
“…The ACGIH has recommended a value of 50 µg/L in venous blood, collected prior to last shift of workweek 3) , as a biological index equivalent to the TLV of 188 mg/m 3 toluene. The ACGIH proposal has been confirmed by many researches and is in accordance with laboratory simulation models of exposure [22][23][24][25][26][27] . The in vitro blood/air partition coefficient for toluene at 37°C reported by the ACGIH Documentation of the biological exposure indices was included between 11.2 and 15.6 28) .…”
Section: Discussionsupporting
confidence: 55%
“…It is unlikely that the end-of-shift blood levels of toluene in the female workers were abnormally elevated. Blood toluene levels are similar to the endof-shift levels determined by Brugnone et al (1995) in which the workers studied are presumed to have been of non-Asian descent. However, Brugnone and co-workers calculated a preshift blood level of 0.1 mg/liter 16 hr after prior exposure.…”
Section: Discussionmentioning
confidence: 90%
“…Toluene in venous blood has been reported as the most reliable and sensitive marker of exposure (Kawai et al, 1994;Brugnone et al, 1995). Mizunuma et al (1994) found blood toluene to be highly correlated to toluene in air at levels (<1 ppm) where hippuric acid was no longer useful.…”
Section: Biomarkers Of Exposurementioning
confidence: 96%
“…For all analytes that have been evaluated by both groups, the levels reported in the United States (44) are lower than the levels reported in Italy (17,25,35,36 Figure 3. Of the members of this population, 96% had blood levels that were above the detection limit of 73 ppt (ng/l), and 75% of those with detectable concentrations had blood levels of 1000 ppt or less.…”
Section: Reference Rangementioning
confidence: 81%
“…These results demonstrate that for some VOCs, decontaminating the sample collection materials is critical if blood concentrations are to be determined accurately. Angerer et al (18) suggested that samples can be frozen at liquid nitrogen temperatures, but in most cases, samples have been stored at 40C (17,22,24). Freezing the samples will lyse the red blood cells and may change the equilibrium within the matrix.…”
Section: Methods Considerationsmentioning
confidence: 99%